Academic and Career Expectations of Ethnic Minority Youth in Hong Kong. (November 2015) - Cheung, Francis; Lai, Beatrice P.Y.; Wu, Anise M. S.; Ku, Lisbeth
Based on social-cognitive career theory (SCCT), we explore how ethnic identity, parental occupation, efficacy in learning Chinese, and learning experience relate to ethnic minority adolescents' academic and career expectations. The participants are 632 Southeast Asian adolescents in Hong Kong. In accordance with SCCT, structural equation modeling results show that ethnic identity is related to learning experience, which in turn is associated with efficacy in learning Chinese. Efficacy in learning Chinese significantly predicts the adolescents' academic and career expectations, but parental occupation does not. Testing of alternative models also shows that ethnic identity is directly related to the two outcome expectations. We discuss the implications and limitations of the study in the context of extending SCCT to a more interdependent culture and assessing factors that contribute to outcome expectations of ethnic minority groups.